1983
DOI: 10.1530/jrf.0.0690057
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the inhibitory effects of hyperprolactinaemia on the mechanism controlling LH secretion in chronically ovariectomized rats

Abstract: The time-course of the inhibitory effect of hyperprolactinaemia on LH secretion was delineated. Hyperprolactinaemia was induced in ovariectomized rats with injections of domperidone or ovine prolactin and circulating LH levels were measured from 1 h to 9 days after the treatment. Inhibition of LH secretion occurred within 2-4 h after treatment, and was maintained (provided that serum prolactin remained elevated) for a period of 6 days only. Thereafter LH levels increased to become insignificantly different fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…However, most reports in the literature showed an inverse relationship between prolac tin and LH [8,9,20], The discrepancies could be due to the above-mentioned differences in blood collection and in the strain used. Also whereas our studies used presum ably stress-free blood withdrawal through chronic venous catheters, other groups obtained blood samples by cardiac puncture under ether anesthesia [26], which greatly alters the circulating concentration of various hormones which include prolactin [8,27] and gonadotropins [28], Hyper prolactinemia induced pseudopregnancy that can in fluence the responses of the hypothalamic pituitary axis to cyclosporine as compared to the control animals in agree ment with previous data from the literature using other stimuli [29].…”
Section: Discussionsupporting
confidence: 84%
“…However, most reports in the literature showed an inverse relationship between prolac tin and LH [8,9,20], The discrepancies could be due to the above-mentioned differences in blood collection and in the strain used. Also whereas our studies used presum ably stress-free blood withdrawal through chronic venous catheters, other groups obtained blood samples by cardiac puncture under ether anesthesia [26], which greatly alters the circulating concentration of various hormones which include prolactin [8,27] and gonadotropins [28], Hyper prolactinemia induced pseudopregnancy that can in fluence the responses of the hypothalamic pituitary axis to cyclosporine as compared to the control animals in agree ment with previous data from the literature using other stimuli [29].…”
Section: Discussionsupporting
confidence: 84%
“…PRL exerts an influence on a number of brain functions [1, 2], such as reproduction [3], sexual behavior [4, 5], feeding behavior [6]and maternal behavior [7]. In addition, PRL acts at the cellular level to regulate GnRH secretion [8, 9, 10], the firing rate of hypothalamic neurons [11], the metabolism of neurotransmitters and neuropeptides [12], oxytocin release [13], enzyme activities in neurons [14]and glial cellular proliferation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its diverse effects on peripheral tissues, prolactin (PRL) interacts with the brain [1, 2, 3]to regulate many functions including maternal behavior [4], grooming behavior [5], sexual behavior [6, 7], feeding behavior [8, 9], reproductive function [10]and sleep/wake cycles [11]. The actions of PRL are presumably mediated by the PRL receptor, a membrane-bound receptor which belongs to the cytokine-hematopoietin receptor superfamily [12].…”
Section: Introductionmentioning
confidence: 99%
“…Since PRL has been shown to regulate maternal behavior [4], sexual behavior [6, 7], feeding behavior [8, 9]and reproductive fertility [10], it is suggested that PRL receptors play essential roles in regulating these physiological changes during lactation. It has been reported that the expression of PRL receptor protein is elevated in specific hypothalamic nuclei during lactation when compared with diestrus [25].…”
Section: Introductionmentioning
confidence: 99%